Ecws-3 2018
DOI: 10.3390/ecws-3-05809
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Bias Correction Methods to Assess the Impact of Climate Change on Flood Frequency Curves

Abstract: Annual maximum daily rainfalls will change in the future because of climate change, according to climate projections provided by EURO-CORDEX. This study aims at understanding how the expected changes in precipitation extremes will affect the flood behavior in the future. Hydrological modeling is required to characterize the rainfall-runoff process adequately in a changing climate to estimate flood changes. Precipitation and temperature projections given by climate models in the control period usually do not fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…This concern introduces larger uncertainty when high return periods T are considered. Such studies point out future changes in flood regimes affecting not only frequency and magnitude of floods, but also a shift in their timing, which might increase the seasonality effects in statistical terms [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…This concern introduces larger uncertainty when high return periods T are considered. Such studies point out future changes in flood regimes affecting not only frequency and magnitude of floods, but also a shift in their timing, which might increase the seasonality effects in statistical terms [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…In the Barrios de Luna, Porma and Riaño catchments, the polynomial bias correction method is selected. However, in Camporredondo, the linear correction provides the best results (Soriano et al 2019).…”
Section: Bias Correctionmentioning
confidence: 97%
“…The results provided by the 12 combinations of GCMs and RCMs of the EURO-CORDEX programme in the four catchments selected as case studies present significant biases in the control period compared with the observations in the same period. Soriano et al (2019) identified the best bias correction techniques for precipitation and temperature projections in the four catchments that have been applied in this study. The daily temperature projections in the control and future periods have been corrected by using a monthly bias correction that depends on the climate model considered (Eq.…”
Section: Bias Correctionmentioning
confidence: 99%
See 2 more Smart Citations